Hippo [videorecording (Blu-Ray)] - Rapaport, Mark; Farley, Kimball; Kizlinger, Lilla; Roberts, Eliza (Hippo llc., 2023)
The story of the coming-of-age of two stepsiblings: Hippo, a video-game addicted teenager and Buttercup, a Hungarian Catholic immigrant with a love of classical music and Jesus. Like the Ancient Greek Aphrodite, Buttercup's love is unrequited by a young man who prefers to indulge the art of war and chaos.